2010
DOI: 10.1152/ajpregu.00235.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gastric distension on blood pressure and superior mesenteric artery blood flow responses to intraduodenal glucose in healthy older subjects

Abstract: Postprandial hypotension occurs frequently and is associated with increased morbidity. Gastric distension may attenuate the postprandial fall in blood pressure (BP). Using a barostat, we sought to determine the effects of gastric distension on BP, heart rate (HR), and superior mesenteric artery (SMA) blood flow responses to intraduodenal glucose in eight (6 men, 2 women) healthy older (65-75 yr old) subjects. BP and HR were measured using an automated device and SMA blood flow was measured using Doppler ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
41
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 37 publications
3
41
2
Order By: Relevance
“…2008; Vanis et al. 2010). That the fall in BP is less following oral, when compared with an identical duodenal, glucose load, in healthy older subjects is likely to reflect the “protective” effects of gastric distension (Gentilcore et al.…”
Section: Introductionmentioning
confidence: 99%
“…2008; Vanis et al. 2010). That the fall in BP is less following oral, when compared with an identical duodenal, glucose load, in healthy older subjects is likely to reflect the “protective” effects of gastric distension (Gentilcore et al.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy older individuals and patients with type 2 diabetes, the postprandial fall in BP and increase in superior mesenteric artery (SMA) blood flow are greater when the rate of gastric emptying (GE), or intraduodenal glucose infusion, is relatively faster [11,12], while gastric distension attenuates the fall in BP [13]. GE in healthy individuals exhibits a wide interindividual variation of~4-17 kJ/min (~1-4 kcal/min) [14]; this is increased in diabetes because of the high prevalence of delayed [15], and occasionally rapid, GE [16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in healthy young subjects, intraduodenal glucose infusions at 1, 2, or 3 kcal/min have no effect on blood pressure (41). In contrast to the effects of small intestinal nutrients, gastric distension attenuates the postprandial fall in blood pressure (35,38,44,46). It was initially reported that gastric distension with a balloon linked to a "barostat" device has the capacity to increase blood pressure in healthy young (35) and older (44, 46) subjects.…”
mentioning
confidence: 99%
“…Information about the effects of gastric distension on SMA blood flow in animals and humans is limited and inconsistent, ranging from no effect (43) to increases (11, 25, 43) and decreases (30,43,46).…”
mentioning
confidence: 99%
See 1 more Smart Citation